Plants Used in Antivenom Therapy in Rural Kenya: Ethnobotany and Future Perspectives - Timothy Omara (Journal of Toxicology)
Snake envenomation is one of the neglected tropical diseases which has left an intolerable death toll and severe socioeconomic losses in Kenya. In a continued effort to identify some antiophidic East African botanical species, this study generated ethnobotanical information on antivenom plants reported in Kenya, with a view to identify potential species which could be subjected to in vitro and clinical studies for possible development into antivenoms. Data retrieved through searches done in multidisciplinary databases (Scopus, Web of Science, PubMed, Science Direct, Google Scholar, and Scientific Electronic Library Online) indicated that 54 plant species belonging to 45 genera, distributed among 27 families, are used for the management of snakebites in Kenya. Most species belonged to the family Asteraceae (11%), Malvaceae (11%), Fabaceae (9%), Annonaceae (6%), Combretaceae (6%), and Lamiaceae (6%). The main growth habit of the species is as herbs (35%), shrubs (33%), and trees (28%). Ethnomedicinal preparations used in treating snake poisons are usually from leaves (48%), roots (26%), and stem bark (8%) through decoctions, infusions, powders, and juices which are applied topically or administered orally. The most frequently encountered species were Combretum collinum, Euclea divinorum, Fuerstia africana, Grewia fallax, Microglossa pyrifolia, Solanecio mannii, and Solanum incanum. Indigenous knowledge on medicinal antivenom therapy in Kenya is humongous, and therefore studies to isolate and evaluate the antivenom compounds in the claimed plants are required to enable their confident use in antivenom therapy alongside commercial antivenin sera.